UPAYA PENINGKATAN KEMAMPUAN PEMAHAMAN MATERI ASMAUL HUSNA DENGAN MENGGUNAKAN METODE PEMBELAJARAN KOOPETARIF TIPE JIGSAW - Rizky Ikhwan (Journal of Community Devation, 2025)
This research aims to improve students' learning outcomes in the subject of Asmaul Husna (The Beautiful Names of Allah) in grade 4 at SD Negeri 056648 P. Buaya, Besitang District, Langkat Regency, through the cooperative learning method of jigsaw. The jigsaw cooperative learning method is chosen because it can encourage students to think critically and creatively in solving related problems. By using this method, it is expected to improve students' understanding of the material on Asmaul Husna. Therefore, teachers must be able to use various methods in teaching so that students are interested in the material to be taught. The use of learning methods such as the jigsaw model in Islamic education learning can improve students' understanding of the material presented and achieve satisfactory learning outcomes."